1993
DOI: 10.1136/vr.132.23.575
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial flora of the urinary tract of pigs associated with cystitis and pyelonephritis

Abstract: Twenty-three cases of porcine cystitis and pyelonephritis were examined bacteriologically. Eubacterium suis was found in 21 cases. The isolation of large numbers of Escherichia coli in the upper urinary tract was associated with linear renal scarring. An unidentifiable streptococcus and Enterococcus faecalis were isolated from a case of purulent ureteritis, pyelitis and pyelonephritis. The bacterial flora from cases of cystitis and pyelonephritis was different from that isolated from sows with asymptomatic bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…Carr & Walton (1992) and Meister (2006) obtained similar results and found the E. coli bacteria as being the most frequent agent among the urine samples evaluated, with 90.38% and 70.45%, respectively. These findings corroborate various other studies that have also found E. coli as the most frequent bacteria in UTI cases in sows (Reis et al 1992, Carr et al 1995, Menin et al 2008.…”
Section: Discussionmentioning
confidence: 57%
“…Carr & Walton (1992) and Meister (2006) obtained similar results and found the E. coli bacteria as being the most frequent agent among the urine samples evaluated, with 90.38% and 70.45%, respectively. These findings corroborate various other studies that have also found E. coli as the most frequent bacteria in UTI cases in sows (Reis et al 1992, Carr et al 1995, Menin et al 2008.…”
Section: Discussionmentioning
confidence: 57%
“…As reported elsewhere, the urinary tract can be colonised by both specific (ie, A suis ) and non-specific bacteria (eg, E coli , Streptococcus species, Staphylococcus species and Enterococcus species) (Carr and Walton 1993). The lack of isolation of specific bacteria, such as A suis in our study, can be attributed mainly to the use of artificial insemination on Italian farms.…”
Section: Discussionmentioning
confidence: 84%
“…E. coli is one of the most commonly isolated bacteria from sows with pyelonephritis [1,14,17,18], whereas the corresponding bacterial flora of slaughtered finishing pigs has not been thoroughly investigated. However, the role of E. coli can be discussed as Actinobaculum suis , a specific urinary pathogen, is commonly demonstrated in co-infection with E. coli [1,14,17,18] and as the isolation of E. coli from urinary tract tissues may be the result of contamination.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of E. coli can be discussed as Actinobaculum suis , a specific urinary pathogen, is commonly demonstrated in co-infection with E. coli [1,14,17,18] and as the isolation of E. coli from urinary tract tissues may be the result of contamination. To our knowledge no studies have visualized E. coli directly in relation to renal lesions, and very few researchers have made concurrent bacteriological and pathological studies, which would otherwise improve the aetiological diagnose.…”
Section: Introductionmentioning
confidence: 99%